Desenvolvimento de um reator fotoquímico aplicável no tratamento de efluentes fenólicos presentes na indústria do petróleo - Mota, André Luís Novais (2005)
With water pollution increment at the last years, so many progresses in researches about treatment of contaminated waters have been developed. In wastewaters containing highly toxic organic compounds, which the biological treatment cannot be applied, the Advanced Oxidation Processes (AOP) is an alternative for degradation of nonbiodegradable and toxic organic substances, because theses processes are generation of hydroxyl radical based on, a highly reactivate substance, with ability to degradate practically all classes of organic compounds. In general, the AOP request use of special ultraviolet (UV) lamps into the reactors. These lamps present a high electric power demand, consisting one of the largest problems for the application of these processes in industrial scale. This work involves the development of a new photochemistry reactor composed of 12 low cost black light fluorescent lamps (SYLVANIA, black light, 40 W) as UV radiation source. The studied process was the photo-Fenton system, a combination of ferrous ions, hydrogen peroxide, and UV radiation, it has been employed for the degradation of a synthetic wastewater containing phenol as pollutant model, one of the main pollutants in the petroleum industry. Preliminary experiments were carrier on to estimate operational conditions of the reactor, besides the effects of the intensity of radiation source and lamp distribution into the reactor. Samples were collected during the experiments and analyzed for determining to dissolved organic carbon (DOC) content, using a TOC analyzer Shimadzu 5000A. The High Performance Liquid Chromatography (HPLC) was also used for identification of the cathecol and hydroquinone formed during the degradation process of the phenol. The actinometry indicated 9,06⋅1018 foton⋅s-1 of photons flow, for 12 actived lamps. A factorial experimental design was elaborated which it was possible to evaluate the influence of the reactants concentration (Fe2+ and H2O2) and to determine the most favorable experimental conditions ([Fe2+] = 1,6 mM and [H2O2] = 150,5 mM). It was verified the increase of ferrous ions concentration is favorable to process until reaching a limit when the increase of ferrous ions presents a negative effect. The H2O2 exhibited a positive effect, however, in high concentrations, reaching a maximum ratio degradation. The mathematical modeling of the process was accomplished using the artificial neural network technique